Guidelines for Management of Idiopathic Normal Pressure Hydrocephalus: Second Edition - MORI, Etsuro; ISHIKAWA, Masatsune; KATO, Takeo; KAZUI, Hiroaki; MIYAKE, Hiroji; MIYAJIMA, Masakazu; NAKAJIMA, Madoka; HASHIMOTO, Masaaki; KURIYAMA, Nagato; TOKUDA, Takahiko; ISHII, Kazunari; KAIJIMA, Mitsunobu; et al. (Neurologia medico-chirurgica, 2012)
Among the various disorders manifesting dementia, gait disturbance, and urinary incontinence in the elderly population, idiopathic normal pressure hydrocephalus (iNPH) is becoming of great importance. After the publication of the first edition of the Guidelines for Management of Idiopathic Normal Pressure Hydrocephalus in 2004 (the English version was published in 2008), clinical awareness of iNPH has risen dramatically, and the number of shunt surgeries has increased rapidly across Japan. Clinical and basic research on iNPH has increased significantly, and more high-level evidence has since been generated. The second edition of the Japanese Guidelines was thus published in July 2011, to provide a series of timely evidence-based recommendations related to iNPH. The revision of the Guidelines has been undertaken by a multidisciplinary expert working group of the Japanese Society of Normal Pressure Hydrocephalus in conjunction with the Japanese Ministry of Health, Labour and Welfare research project on “Studies on the epidemiology, pathophysiology, and treatment of normal pressure hydrocephalus.” This English version of the second edition of the Guidelines was made to share these ideas with the international community and to promote international research on iNPH.